A Case of Typically Developing Children Aged Two to Seven in Reconstructing Stories - Adella Suvy Fahriyatul Ahkam (Universitas Pendidikan Indonesia (UPI), 2019)
Age and narrative structures are two elements which tend to be used by most researchers in studying language skill. However, most tend to analyze it separately and with older participants. In fact, children have developed this skill since very young age. This study aims to analyze the oral narrative structure in typically developing children aged two to seven, as well as the influencing social factors. This research employs a descriptive qualitative method to describe and investigate the research questions. The findings show that the typically developing children aged two to seven are able to tell story structurally. However, from the six elements of narrative (abstract, orientation, complication, evaluation, resolution, and coda), most of the participating children’s narrations consist of three elements namely abstract, orientation, and complication. Among older ages, their stories become more complete. In addition, from the three central parenting methods consisting of children’s participation in daily routine, engagement between children and caregivers, and appropriateness of material given, the first aspect seems to play the most visible effect in shaping the children’s narrative skills. This study is expected to give contribution in examining narrative skill development, especially in young aged children. Thus, any possibilities of language disorder and impairment in children can be identified and treated earlier. Keywords: narrative structure, narrative development, parenting methods, child characteristics